2017
DOI: 10.2131/jts.42.491
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane is a suitable alternative to ether for anesthetizing rats prior to euthanasia for gene expression analysis

Abstract: Diethyl ether (ether) had been widely used in Japan for anesthesia, despite its explosive properties and toxicity to both humans and animals. We also had used ether as an anesthetic for euthanizing rats for research in the Toxicogenomics Project (TGP). Because the use of ether for these purposes will likely cease, it is required to select an alternative anesthetic which is validated for consistency with existing TGP data acquired under ether anesthesia. We therefore compared two alternative anesthetic candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…We made this substitution owing to the fact that ether is both explosive and known to be toxic in humans and other mammals. In prior studies, no differences in gene expression, hematological findings, or biochemical parameters were observed when comparing treatments with ether, pentobarbital, and isoflurane ( Nakatsu et al, 2017 ). Some researchers have reported that pentobarbital injection can induce additional stress that can interfere with cortisol levels in the plasma ( Wu et al, 2015 ), and acute pentobarbital administration in rats is associated with the impairment of spatial learning, memory, and hippocampal long-term potentiation ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…We made this substitution owing to the fact that ether is both explosive and known to be toxic in humans and other mammals. In prior studies, no differences in gene expression, hematological findings, or biochemical parameters were observed when comparing treatments with ether, pentobarbital, and isoflurane ( Nakatsu et al, 2017 ). Some researchers have reported that pentobarbital injection can induce additional stress that can interfere with cortisol levels in the plasma ( Wu et al, 2015 ), and acute pentobarbital administration in rats is associated with the impairment of spatial learning, memory, and hippocampal long-term potentiation ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…In the experimental procedures of the present work, animals were briefly exposed to isoflurane anesthesia to minimize the discomfort associated with intraperitoneal injection of [U-13 C 3 ]glycerol. Isoflurane is generally acceptable in rat experiments without causing noticeable alterations in liver metabolism (6,20,21). However, continuously inhaled isoflurane with the use of bolus propofol anesthesia was reported to cause hepatic insulin resistance in dogs (17).…”
Section: E549mentioning
confidence: 99%
“…In this study, we have used ether for euthanasia, which was reported to have an effect on inducing stress via releasing prolactin (Bodosi et al, ). However, a recent study has found that there are no significant differences among ether, isoflurane, and pentobarbital with respect to the effects on hematological parameters, serum biochemistry parameters, and gene expression (Nakatsu et al, ). Nevertheless, further studies are needed to fully understand the effect of different euthanasia inducers on the outcome of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%